Managing Cancer Pain - Simple Rules, Major Benefits - Dwight E Moulin (Pain Research and Management)
In the developed world, approximately one in three individuals will be diagnosed with cancer and one-half of those will die of progressive disease (1). At least 75% of patients with cancer develop pain before death. It is therefore not surprising that pain is one of the most feared consequences of cancer for both patients and families (2). The good news is that cancer pain can be controlled with relatively simple means in more than 80% of cases based on guidelines from the World Health Organization (3). Mild pain can be treated with acetaminophen or nonsteroidal anti-inflammatory drugs (Step 1 of the analgesic ladder). Moderate pain requires the addition of a 'minor' opioid such as codeine (Step 2), and severe pain mandates the use of a major opioid analgesic such as morphine (Step 3). In this issue of Pain Research & Management, Gallagher et al (pages 188-194) highlight some of the barriers to adequate cancer pain management based on a cross-sectional survey of British Columbian physicians. The survey response rate of 69% attests to the validity of their findings.